Social-pedagogical aspects resocialization of pupils of the centers social-psychological rehabilitation of children - Piduyra, Ivan; Vainola, Renata (ScienceRise: Pedagogical Education, 2017)
The article substantiates the notion of pedagogical support of resocialization of pupils of centers of social-psychological rehabilitation of children as a complex of pedagogical means, mechanisms and forms of their realization. This support favors the activation of own experience and potential of pupils. It also widens possibilities of the learning-upbringing system of centers of social-psychological rehabilitation of children for increasing the effectiveness of the process of pupils’ resocialization. There were characterized the components of the pedagogical support of the process of resocialization of pupils of centers (aim, principles, content, directions, mechanisms and forms of their realization). The aim of the pedagogical support of the process of resocialization of pupils of centers is to favor the overcoming of obstacles or lag in the process of children’s socialization using the complex of correcting-rehabilitating forms of the social-pedagogical work. There were determined the principles of the pedagogical support of resocialization of pupils of centers: the principle of purposefulness, reflexivity, partnership, subjectivity, synergy, unity of the learning, upbringing and correcting work at realizing resocialization tasks. There were separated the content directions of the pedagogical support: – formation and assimilation of democratic culture skills; – realization of civic duties; – taking of responsibility (for oneself, family, society); – formation of integral worldview; – mastering of social skills; – conscious choice of life strategies; – realization of rights, possibilities and motivation of the future social and professional development; – development of communication skills, communication culture; – development of self-cognition, self-appraisal, self-determination. There were determined the mechanisms of introduction of the pedagogical support of the process of resocialization of pupils of centers of social-psychological rehabilitation of children: – mechanism of favoring pupils’ participation in the process of resocialization; – mechanism of activation of the work of social teachers and psychologists of centers; – mechanism of involving, parents, persons, who replace them and tutors of pupils of centers to the cooperation in the direction of resocialization. The effectiveness of the elaborated pedagogical support of the process of recosialization of pupils of centers and forms of the social-pedagogical work with them was proved. There were presented the complex program of resocialization of pupils of centers “You are able to more!”, forms of the social-pedagogical work with parents (persons, who replace them) of pupils and specialists of centers of social-psychological rehabilitation of children (lecture, pedagogical seminar)